EVALUASI KEBIJAKAN PERATURAN DESA TENTANG KAWASAN BEBAS MEROKOK (Studi Kasus Kawasan Tempat Umum Desa Carawali) - Wirandi Wirandi Wirandi; Sahar Sahar (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2020)
Abstract The purpose of this study was to find out the Village Evaluation Policy (Perdes) of Carawali concerning the Wattang Pulu Smoking-free Zone in Sidenreng Rappang District and the factors that influenced the Carawali Village Regulation Policy Evaluation concerning the Smoking-Free Zone in Wattang Pulu District, Sidenreng Rappang District. The population was 1193 people in the village of Carawali, the sample in this study was 60 people of the village of Carawali, based on random sampling techniques or random samples with sampling techniques using the yount formula. This type of research is quantitative descriptive with basic research, survey research with descriptive explanatory level, and the type of data in this study is quantitative research, data sources from this study are primary and secondary, data collection techniques used in this study are observation, questionnaire / questionnaires, interviews, and documentation. The results of the Carawali Village Regulation (Perdes) Policy Evaluation of the Wattang Pulu District Non-Smoking Area in Sidenreng Rappang Regency are in the